Untold secret of effective management process in community service activities at orphanage center - Shaik Alaudeen, Muharratul Sharifah; Rahman, Khairunnisa; Azmi, Nurul Azlin; Mamat@ Mohd Nor, Farizah (Universiti Teknologi MARA, Kedah, 2024)
Children are the future generation and will contribute to the development of the country. A good education and nurturing from family is crucial to producing high-quality future generations for a better country’s development. However, some children are unfortunate and become orphaned at a young age. A lot of community services and corporate social responsibility activities are done by individuals, private companies, and universities for various purposes to shape the children in the orphanage to become better people. This study investigated the management process and effectiveness of a workshop on the mental, emotional, and self-management of orphanage children in Johor. The workshop was handled by a team of management lecturers, a professional counsellor, and a medical psychiatric expert. The attendees are orphaned children aged from 5- 18 years old. An observation showed that certain management needs to be addressed for community service to be performed at an orphanage center such as objectives of activity, form of activities, duration of task, and authority that need to be acknowledged before and during the activities. Community service activities designed according to the management process can have good and effective programs at orphanage centers.